PENGARUH REFORMASI BIROKRASI TERHADAP PERIZINAN PENANAMAN MODAL DI DAERAH (Studi Kasus Di Pemerintahan Kota Bekasi) - Suwari Akhmaddhian (Faculty of Law, Universitas Jenderal Soedirman, 2012)
Bureaucratic reform is essentially an attempt to reform and fundamental changes to the system of governance in order to reach the goal of bureaucratic reform to accelerate achievement of good governance and efforts to improve support for local government in increasing performance. Bureaucracy reform program runs which is principally consisted of institusional reform, human resources reform and management information technology support in the licensing process. Institutional reform is by estabilishing a new agency that handles the licensing process in the past, licensing process has to go through the different agencies and with the reform of the bureaucracy in the licensing process united in one body that is unified, improve human resources through training and increase the transparency of information through the management information technology support. Bureaucratic reform in investment licensing in the area is already under way in an effort to improve the service to the community, so good governance is not just a dream and soon will become a reality. Key words: licensing, service, bureaucratic reform.